1974
DOI: 10.1159/000136524
|View full text |Cite
|
Sign up to set email alerts
|

Central Effects of Three Fluorinated Benzodiazepines in Comparison with Diazepam

Abstract: The central effects of the 5-(o-fluorophenyl)-3-hydroxybenzodiazepines SAS 643, SAS 646 and Ro 7–5205 were investigated and compared with those of diazepam. It was found that, in rats, these drugs have a pharmacological profile very close to that of diazepam. They possessed a high antimetrazol activity, a muscle-relaxant effect and a depressive action upon exploratory behavior. Moreover, they facilitated behavior suppressed by punishment and caused a synchronization of the EEG pattern. With regard to the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…The same finding was reported by Babbini et al [16] in an anti-pentetrazol test, where introduction of a longer side chain to position 1 reduced the potency. Babbini et al [16] also demonstrated that there was no remarkable difference between a hydrogen group and methyl group at position 1 for anti-pentetrazol activity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The same finding was reported by Babbini et al [16] in an anti-pentetrazol test, where introduction of a longer side chain to position 1 reduced the potency. Babbini et al [16] also demonstrated that there was no remarkable difference between a hydrogen group and methyl group at position 1 for anti-pentetrazol activity.…”
Section: Discussionsupporting
confidence: 86%
“…The same finding was reported by Babbini et al [16] in an anti-pentetrazol test, where introduction of a longer side chain to position 1 reduced the potency. Babbini et al [16] also demonstrated that there was no remarkable difference between a hydrogen group and methyl group at position 1 for anti-pentetrazol activity. However, in the present amygdaloid-kindled seizures, the compounds having a hydrogen group at position 1 had a more potent effect than the compounds with a methyl group at the same position (lorazepam vs. lormetazepam; nitrazepam vs. nimetazepam).…”
Section: Discussionsupporting
confidence: 86%
“…Though the effect of the parent compounds, diazepam and clorazepate, are uncertain because of the activity of their common metabolite, nordiazepam, the activity (Randall, Scheckel & Pool, 1970;Marcucci, Mussini, Guaitani, Famelli & Garattini, 1971;De Angelis, Traversa & Vertua, 1974;Babbini, Torielli, Gaiardi, Bartoletti & De Marchi, 1974;Babbini, Gaiardi, Bartoletti, Torielli & De Marchi, 1975 …”
Section: Discussionmentioning
confidence: 99%
“…The method has been already described elsewhere (4). Four doses of each drug were tested using 4 -7 animals per dose level.…”
Section: Methodsmentioning
confidence: 99%